Pigmented Villonodular Synovitis of the Thoracic Vertebra Presenting with Progressive Spastic Paraparesis. (15th September 2013) - Celiktas, Mustafa; Asik, Mehmet Ozan; Gezercan, Yurdal; Gulsen, Mahir
Abstract : Pigmented villonodular synovitis (PVNS) is a proliferative benign lesion originating from the synovium and commonly affects large joints of the extremities. PVNS can arise from any synovium in the whole body and rarely affects the zygapophyseal joints of the spine. Spinal PVNS is diagnosed mostly after resection of the mass. In our case we present a 22-year-old male patient showing progressive spastic paraparesis with insidious onset of back pain and difficulty of walking in a relatively short period of 1 month. After gross excision of the mass, diagnosis was established through histopathology. Two years of follow-up period reveals complete resolution of the patient's complaints and no recurrence on radiologic images.